The meaning of behavioral medicine in the public health field—a review of documents related to medical education in Japan. Issue 1 (December 2016) - Inoue, Shigeru
Abstract International standardization of medical education requires Japanese medical schools to restructure their curricula to include "behavioral science." Two influential documents for Japanese medical education, the "Model Core Curriculum for Medical Education in Japan" and the "Scope of the Japanese National Examination for Medical Doctors" include some key terms regarding behavioral science. However, they are not systematic and the phrase "behavioral science" itself could not be found in these documents. The new global standards for medical education, the "Basic Medical Education WFME Global Standards, " require medical schools to include behavioral science in their curricula. The definition of "behavioral science" in the global standards emphasizes social aspects and determinants of health, which is also a key concept of public health. From the view point of public health, it is hoped that the systematic introduction of behavioral science into Japanese medical education will strengthen the public health mindset of medical doctors, which in turn will support the healthcare system in communities.